1925. Sheikh Saeed al-Piran Revolution between Religious and National Identity - Abdulrahman, Prof.Dr.Pshko Hama Tahir (Sulaimani Journal for Humanities, 2025)
The North Kurdistan Revolution, which was planned by the Independence/Liberty Association, was later led by Sheikh Saeed Piran, this revolution was expected to start on (21th, March 1925), but it was begun ahead its appointed time. This revolution was able to cover a large part of North Kurdistan and many citizens followed the call of the revolution. The Turks, after taking several military steps, could not completely suppress the revolution, so they launched an international conspiracy against the revolution and proclaimed that it was a conservative revolution and they wanted to revive the caliphate, So they were able to eliminate international support for the revolution and put an end to it. After a century, this revolution is the subject of much debate. Is it religious or national? In this study, we want to correct all the conspiracies and writings that call this revolution conservative, which in fact, according to all the real documents and writings, the revolution was a national revolution and its goal was an independent Kurdistan.